2016
DOI: 10.1057/mel.2016.5
|View full text |Cite
|
Sign up to set email alerts
|

A new connectivity index for container ports

Abstract: A new connectivity index for container portsJ o h n J B a r t h o l d i I I I a , P i s i t J a r u m a n e e r o j b a n d A m a r R a m u d h i n A b s t r a c t We propose a new index, the Container Port Connectivity Index, to measure the trade connectivity of ports within the network of container shipping. This index is based on both economics and network topology, and a distinctive feature is that the strength of a port is based on its position within the global structure of the shipping network, and not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
1
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 15 publications
(32 reference statements)
1
33
1
2
Order By: Relevance
“…An outstanding example of such impact is the Container Port Connectivity Index developed by Bartholdi et al [5]. This index is a two-metric global port ranking index that uses the concept of eigenvector centrality and the transport economics reflected in United Nations Conference on Trade and Development's long-standing Liner Shipping Connectivity Index, to create a better classification of the roles that global ports play [5,54].…”
Section: Applications Of Complex Network Theory In the Maritime Domainmentioning
confidence: 99%
“…An outstanding example of such impact is the Container Port Connectivity Index developed by Bartholdi et al [5]. This index is a two-metric global port ranking index that uses the concept of eigenvector centrality and the transport economics reflected in United Nations Conference on Trade and Development's long-standing Liner Shipping Connectivity Index, to create a better classification of the roles that global ports play [5,54].…”
Section: Applications Of Complex Network Theory In the Maritime Domainmentioning
confidence: 99%
“…There are many researches that highlight the significant role of maritime ports. Hence, many researchers investigate the importance of port's supply chain integration (Bartholdi et al, 2016;Gumzej & Čišić, 2018;Host et al, 2018;Onwuegbuchunam et al, 2018;Trupac & Twrdy, 2010), their importance for the port-city relationship (Hesse, 2018;Monios et al, 2018;Schiozzi et al, 2018), and hinterland connections (Bergqvist, 2015;Notteboom & Rodrigue, 2007;Van Der Horst & De Langen, 2008). Other emphasize the importance and quality of container shipping liners (El Kalla et al, 2017; Hirata, 2017; Kos et al, 2010) and the importance of working timetable har-and the importance of working timetable harmonization between seaport clusters (Karmelić & Tijan, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In addition, Carruthers (2013) made a benchmark analysis to highlight the importance of transport infrastructure and its impact on the overall country growth. Kevin et al (2004) considered port equipment as an im-considered port equipment as an important input factor for measuring the container port production efficiency through the frequently used data envelopment analysis (Bichou, 2013;Hung et al, 2010;Sharma & Jin, 2009), while Bartholdi et al (2016) suggest-, while Bartholdi et al (2016) suggest- Bartholdi et al (2016) suggest-suggested a new measure of importance with which to compare container ports, the so-called Container Port Connectivity Index. All this, together with additional factors, has a significant influence on port performance.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Single layer studies on transportation systems are extensive covering air transport (Lordan et al, 2016(Lordan et al, , 2015Lordan, 2014;Lordan et al, 2014b;Sun et al, 2017;Zanin et al, 2009;Zanin and Lillo, 2013), maritime networks (Bartholdi and Jarumaneeroj, 2014;Ducruet et al, 2010a,b;Ducruet and Notteboom, 2012;Ducruet, 2016;González Laxe et al, 2012;Hu and Zhu, 2009;Fraser et al, 2014;Mohamed-Chérif and Ducruet, 2016;Pais Montes et al, 2012;Tsiostas and Polyzos, 2015;Viljoen and Joubert, 2016), train, bus, tram and subway systems (Criado et al, 2007;Kurant and Thiran, 2006a;Mouronte and Benito, 2012;Ouyang et al, 2014;Sen et al, 2003), and the structural properties and vulnerability of road networks (Crucitti et al, 2006;Duan and Lu, 2014;Gudmundsson and Mohajeri, 2013;Háznagy et al, 2015;Jiang, 2007;Jiang and Claramunt, 2004;Porta et al, 2012;Reggiani et al, 2011;Rupi et al, 2015;Strano et al, 2009;Zadeh and Rajabi, 2013).…”
Section: Transportation Applicationsmentioning
confidence: 99%